Cognitive asymmetry in rats in response to emergent vs. disappearing affordances - Wojciech Pisula; Klaudia Modlinska; Anna Chrzanowska; Katarzyna Goncikowska (Animal Cognition)
Abstract This study examines the effects of novel environmental changes on the behavior of rats in an experimental chamber. We hypothesized that newly discovered opportunities, detected by the animal’s cognitive system, would motivate greater investigation of environmental changes than comparable changes that prevent a given behavior. Three experiments differed in the emergence vs. elimination of affordances represented by open or closed tunnels. In Experiment 1, rats were habituated to a chamber with all four tunnels closed, and then two tunnels were opened. In Experiment 2, rats were habituated to a chamber where all four tunnels were open, and then two tunnels were closed. In Experiment 3, rats were habituated to a chamber with two open tunnels on one side, and two closed tunnels on the other. Then, the arrangement of open and closed tunnels was swapped. Results of the Exp. 1 show that the rats responded by spending more time near the newly opened tunnels and less time near the closed tunnels, the central zone, and the transporter. This suggests that rats are more motivated to investigate the environmental change combined with the emergent affordance (opening of the tunnels) than the environmental change alone. In Exp. 2, the rats responded by spending more time near the open tunnels and less time in the central zone. This suggests that the rats are more triggered by the available affordances (open tunnels) than by the environmental change (closed tunnels). Finally, in Exp. 3, the rats responded by spending more time near the newly opened tunnels and less near the central zone. However, they did not spend less time near the newly closed tunnels. These results suggest that rats process both the novelty itself and the emergence/disappearance of available affordances. The results are discussed regarding the cognitive asymmetry in the perception of emergent vs. disappearing affordances. It is proposed that the rat’s cognitive system is specialized for detecting newly emergent environmental opportunities/affordances rather than novelty in general.